(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Information literacy (IL) education in Malaysia is officially integrated into the school curriculum. However, it seems that the development and progress of ILE implementation are slower than might be expected. Thus, the goal of this qualitative study is to determine the factors affecting the implementation of IL education in Malaysian primary schools and to explore how these factors are facilitating or hindering the process. Case studies were conducted involving two national primary schools representing one of the two public school types in Malaysia. In-depth, semi-structured interviews were held with school teachers and key stakeholders followed by documentary analysis for further understanding of the implementation issues emerging during the implementation. From the analysis of the transcripts of the interviews with teaching staff, a range of factors hindering and facilitating IL education implementation has been identified. Interview data shows that most participants had positive attitudes towards IL education. They believed that IL education was important and had the potential to make teaching and learning activities more engaging and fun. However, the participants also reported that there were problems in implementing ILE; these problems seem to be associated with the school ecology.